A musculoskeletal modelling approach of the assessment of the risk of hamstring injuries in professional soccer players: a pilot study - Ménard, M.; Sorel, A.; Boumpoutou, R.; Kulpa, R.; Kerhervé, H. A.; Bideau, B. (Science and Medicine in Football, 2021)
Purpose: Evaluating and minimising the risk of hamstring injury remains complex as it lacks reliable field-testing. Kinematic analysis provides global external insights but fails to apprehend musculoskeletal loading. This study aimed to evaluate the association between hamstring function and prior injury using a novel functional test combined with a musculoskeletal approach.